Rice seed health: (International Rice Research Institute, 1988)
This proceeding consists of papers presented on the International Workshop on Rice Seed Health 16 - 20 March 1987. These papers are devided into 7 groups: overview of rice seed health and production issues; Regional and national plant quarantine systems; Rice pests of quarantine importance; Seed health research in rice; Seedborne and seed - transmitted pests in rice-based cropping systems ; The rice seed production system ; and Seed production and technology